DISSEMINATION OF APPLICATION OF COW FEED PRODUCTION MACHINERY EQUIPMENT IN KAYEE LEE VILLAGE, INGIN JAYA DISTRICT, ACEH BESAR - Darwin, Darwin; Rizal, Muhammad (LPPM Univ. Ibn Khaldun Bogor, 2023)
In this product-based community service activity, the service team offers several concrete and tangible solutions to overcoming the problem of difficulties in obtaining ruminant feed. The solution offered is to build a portable silage machine tool system. The installation of this machine tool is an application of bioprocess technology where this equipment system is not only equipped with a biomass chopping machine but is also equipped with a biofermentor installation that can produce silage which is animal feed from fermented biomass rich in nutrients that are needed for increasing cow weight. Thus the equipment and machines designed can be a targeted solution in overcoming the shortage of animal feed for ruminant animal breeders in one of the assisted villages of Syiah Kuala University, namely Kayee Lee Village, and can also improve the skills and knowledge of farmers in producing animal feed independently and sustainable.